FINANCIAL PERFORMANCE ANALYSIS on KOPMA UNS SURAKARTA PERIOD in 2013 – 2016 BASED on the REGULATIONS of the STATE MINISTER of COOPERATIVES and SMALL and MEDIUM ENTERPRISES RI NUMBER 20/Per/m. KUKM/XI/2008 - Juli Hariyanto; Burhanudin Burhanudin; Rochmi Widayanti (Econosains Jurnal Online Ekonomi dan Pendidikan, 2018)
The purpose of this study is to analyze and find out the financial performance on March Eleven University students Cooperative Surakarta year 2013 – 2016 views of awarding a score of 7 aspects of the cooperative assessment. Researchers using this type of qualitative descriptive study, with financial ratio analysis techniques using a regulation of the Minister of the Cooperative Republic of Indonesia No. 20/Per/m. KUKM/XI/2008. This research is located in Eleven University students Cooperative March (KOPMA). The Data used are secondary data, data obtained from the financial reports KOPMA UNS Surakarta from 2013 – 2016. The results of the research, the UNS Surakarta KOPMA financial performance from the year 2013 to 2016 including the criterion of "pretty healthy" with a total value of score an average of 65.10. In the year 2013 is quite healthy with total value of score 64.60, the year 2014 is quite healthy with total value of score 64.85, the year 2015 is quite healthy with total value of score 62.60, and in 2016 is quite healthy with total value of score 68.35. Keywords: financial performance, 7 aspects of the cooperative assessment.